Banking Sector Stability in Sierra Leone: An Econometric Analysis - Johnson, Leroy (International Journal of Scientific Research and Management (IJSRM), 2022)
This study assess banking sector stability in Sierra Leone using quarterly data over the period 2009-2019 of the fourteen banks in the sector. The study was carried out in the context of Johansen Cointegration estimation technique and it was found out that in the long run, total bank assets, gross loans positively influence banking sector stability whilst exchange rate had negative effect on banking sector stability. In the short run, total banking assets was also found to have a positive and statistically significant relationship. Arising from theaforementioned estimation results, this study recommends that banks transition to Basel three Capital Framework which is forward looking that shore up the stability of the banking sector and makes provisions for risks that will emanate in the banking realms of Sierra Leone. This is turn will facilitate smooth banking operations and fortifies public confidence in the banking sector.